BRAF V600E does not predict aggressive features of pediatric papillary thyroid carcinoma. (29th April 2014) - Givens, Daniel J.; Buchmann, Luke O.; Agarwal, Archana M.; Grimmer, Johannes F.; Hunt, Jason P.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis This study aimed to review the prevalence of the BRAF V600E mutation in pediatric papillary thyroid carcinoma (PTC) and any possible association with aggressive tumor behavior. Study Design A retrospective chart review and post hoc BRAF V600E mutational analysis of archived tumor tissue. Methods Patients 0 to 18 years old who underwent surgery for PTC from 1999 to 2012 were selected for a retrospective chart review to assess for aggressive disease characteristics. Microdissection was performed on archived tumor tissue, which was analyzed for the BRAF V600E mutation by pyrosequencing. Results Archived tumor specimens were available for 19/27 pediatric patients who fit the inclusion criteria. Ages ranged from 2.8 to 18 years (median, 13.7 years). Thirteen patients (68.4%) had central neck metastases, eight (42.1%) had lateral neck metastases, and five (26.3%) had pulmonary metastases. The BRAF V600E mutation was present in seven patients (36.8%). There were 11 patients with classic PTC, seven with a follicular variant of PTC, and one with an oncocytic variant. Seven (63.6%) with classical PTC were BRAF V600E positive. All histologic variants were wild type. PTC histology significantly correlated with the BRAF mutation (P = .013). The BRAF mutation was associated with a lower metastases, age at diagnosis, completeness of resection, invasion, and size of the tumor score, which trended toward significance (P = .087). Presence of lymphatic or pulmonary metastases, tumor size, overall age, lymphovascular invasion, or extrathyroidal extension were not associated with BRAF V600E. Our results are combined with existing studies for a combined incidence of 28.4%. Conclusions BRAF V600E mutations may be more prevalent than previously thought in pediatric patients with PTC, but do not correlate with aggressive disease characteristics. Level of Evidence 4. Laryngoscope, 124:E389–E393, 2014